DISFUNGSI EREKSI MENYEBABKAN DEPRESI PADA KLIEN DIABETES MELLITUS TIPE II - Ida Farida; Ati Nuraeni (Poltekkes Kemenkes Bandung, 2020)
Long-standing diabetes can lead to various complications such as heart disease, stroke, neuropathy. Clients diabetes mellitus men may suffer from erectile dysfunction. According to research conducted by Virani, Chandola and jadeja of 53 male clients with diabetes experience erectile dysfunction 69.81% .. These circumstances make the clients can not meet their basic needs which include biological needs, social, spiritual, and psychological (Hidayat, 2008). One of the psychological disorders experienced by clients diabetes with erectile dysfunction is depression. This study was conducted to analyze the relationship between erectile dysfunction and depression as well as other factors that influence it. The design of the study is cross-sectional. The data collection begins with erectile dysfunction screening questionnaire International Index of Erectile Function (IIEF). In these two groups was measured using the instrument BDI depression (Beck Depression Inventory) and other variables suspected as confounding as age, duration of diabetes mellitus, blood pressure, fasting blood sugar with interview techniques using a questionnaire. Statistical test results showed that there was a connection between erectile dysfunction and depression (p-value 0.03). When a DM with severe dysfunction have a chance of severely depressed by 8 times greater than with a DM who experience mild erectile dysfunction. At the 95% confidence level the chances of a DM who experience severe erectile dysfunction can severely depressed by 1- 63 times greater than with a DM mild erectile dysfunction. It is expected that nurses should educate the DM client to help control blood sugar, then complications such as erectile dysfunction can be prevented, so that a good sexual activity can have a positive effect on physical and mental health.